PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR SEMEN YANG TERDAFTAR DI BEI 2015 - 2019 - Puji Deli Shella; Lorina Siregar Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This study aims to test whether liquidity and leverage have an effect on. The object in this study is a cement sub-sector manufacturing company listed on the Indonesia Stock Exchange in 2015-2019 consisting of 6 companies sampled in this study. This study uses secondary data processed using SPSS 26 application. The results of the research obtained in this study stated that liquidity (CR) and leverage (DER) have a significant effect on profitability (ROA) in cement sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2019.